The Future of Construction: Integrating Innovative Technologies for Smarter Project Management - Dagou, Houljakbe Houlteurbe; Gurgun, Asli Pelin; Koc, Kerim; Budayan, Cenk (MDPI, 2025)
The construction industry is transforming significantly, with emerging technologies reshaping project management by enhancing efficiency, sustainability, and safety. This study examines the integration of these innovations into Chad's construction sector, drawing on insights from 79 industry participants. Given Chad's unique economic and infrastructural landscape, understanding the practical implementation of these technologies is crucial. This research demonstrated strong reliability and validity through exploratory factor analysis, with a KMO value above 0.75, statistical significance at p < 0.001, and a Cronbach's Alpha exceeding 0.8. Using Promax rotation, this study identified 15 key factors, providing valuable insights into how technologies such as Building Information Modeling (BIM), Artificial Intelligence (AI), the Internet of Things (IoT), and Digital Twin technology are transforming construction processes. These tools enhance design accuracy, facilitate real-time decision-making, and minimize material waste while supporting global sustainability goals, including the United Nations' Sustainable Development Goals (SDGs). Examining the adoption of these technologies within Chad is particularly important, as the country faces unique challenges that demand tailored solutions. While digital transformation in the construction industry has been widely studied worldwide and in Africa, Chad's industry remains relatively unexplored in this regard. This research bridges this gap by identifying both the opportunities and the barriers to technological integration in the sector. Embracing these innovations could help modernize Chad's construction industry, addressing persistent inefficiencies and promoting environmental sustainability. However, widespread adoption is hindered by significant challenges, including high implementation costs, limited access to advanced tools, and a shortage of skilled professionals. Overcoming these obstacles will require strategic investments in education, infrastructure, and supportive policies. By fully leveraging technological advancements, Chad has the potential to build a more competitive, resilient, and sustainable construction industry, driving national development while aligning with global sustainability initiatives.
Keywords: innovative technologies; sustainability; project management; smart infrastructure; resource management; SUSTAINABLE DEVELOPMENT GOALS; EXPLORATORY FACTOR-ANALYSIS; BLOCKCHAIN TECHNOLOGY; INDUSTRY 4.0; ENERGY; IMPACTS; SUCCESS; SYSTEMS; SECTOR; AGENDA; Science & Technology - Other Topics; Environmental Sciences & Ecology